Social Security and Inflation: A Study of the Economic Effects of an Adjustable Pensions Scheme - Peacock, Alan T. (Review of Economic Studies, 1952)
Journal Article Social Security and Inflation: a Study of the Economic Effects of an Adjustable Pensions Scheme Get access Alan T. Peacock Alan T. Peacock London Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 20, Issue 3, 1952, Pages 169–173, https://doi.org/10.2307/2295886 Published: 01 January 1952